Methodological quality, completeness of reporting and use of systematic reviews as evidence in clinical practice guidelines for paediatric overweight and obesity. (February 2017) - Nissen, T.; Wayant, C.; Wahlstrom, A.; Sinnett, P.; Fugate, C.; Herrington, J.; Vassar, M.
Summary: Paediatric obesity rates remain high despite extensive efforts to prevent and treat obesity in children. We investigated the quality of the methodology and reporting within systematic reviews (SRs) underpinning paediatric content in US clinical practice guidelines (CPGs). In June 2016 we searched guideline clearinghouses and professional organization websites for guidelines published by national or professional organizations in the United States from January 2007 onwards. In our primary, a priori analysis, we used PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) and AMSTAR (A Measurement Tool to Assess Systematic Reviews) instruments to score SRs and meta‐analyses that included paediatric populations and were cited by included CPGs. In a secondary, post hoc analysis, we determined the extent to which US CPGs use available, relevant SRs and meta‐analyses compared with non‐US CPGs. Eight US‐based CPGs with 27 references to 22 unique SRs were found. AMSTAR and PRISMA scores were low overall, with only three SRs having 'high' methodological quality. Items dealing with bias assessments and search strategies had especially low scores. US CPGs were also older on average and cited fewer SRs than their international counterparts. Low quality scores and dated guidelines should be a cause for concern among practicing clinicians and a call to action for future guideline developers, publishers and research institutions.